2014
DOI: 10.1097/aco.0000000000000032
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral protection

Abstract: Recent research points to a central role of a neuro-inflammatory cascade in POCD, with endothelial dysfunction potentially aggravating the insult. Investigating the genomic and molecular mechanisms that underlie the intervariation in the inflammatory response to surgery, improving the identification of appropriate endothelial and inflammatory biomarkers, and developing endothelial modulatory and anti-inflammatory (prevention and resolution) strategies are key areas of future translational research. This is imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(34 citation statements)
references
References 59 publications
(43 reference statements)
1
29
0
2
Order By: Relevance
“…Many mental disorders are associated with both a loss of PFC synapses and increased signs of neuroinflammation e.g. ( Pace and Heim, 2011 , Raison and Miller, 2013 , Yoshiyama et al., 2007 , Schizophrenia Working Gro, 2014 , Sharma et al., 2014 , Riedel et al., 2014 , Masi et al., 2014 ). Given that guanfacine can protect working memory ( Birnbaum et al., 2000 ) and PFC dendritic spines, as well as reducing inflammation, it may be helpful across a wide spectrum of mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Many mental disorders are associated with both a loss of PFC synapses and increased signs of neuroinflammation e.g. ( Pace and Heim, 2011 , Raison and Miller, 2013 , Yoshiyama et al., 2007 , Schizophrenia Working Gro, 2014 , Sharma et al., 2014 , Riedel et al., 2014 , Masi et al., 2014 ). Given that guanfacine can protect working memory ( Birnbaum et al., 2000 ) and PFC dendritic spines, as well as reducing inflammation, it may be helpful across a wide spectrum of mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms of POCD are not yet fully understood. Clinical studies have consistently suggested that the main causes of this injury include an exaggerated systemic inflammation [ 6 ], endothelial dysfunction [ 7 ], cerebral hypoperfusion, and microembolism [ 8 ]. Others have specifically reported that POCD is indeed correlated with the serum protein levels of IL-6, TNF-α, S100β, neuron-specific enolase (NSE), and malonaldehyde (MDA) [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Хирургическое вмешательство рассматривается лишь как фактор, запускающий каскад воспалительных реакций, а анестезия, напротив, служит ключевой причиной ПОКД. При этом операция или любая инвазивная манипуляция только усугубляют когнитив-ные нарушения у пациентов, «склонных» к регрессу ментальных функций [28].…”
Section: Keywtrbunclassified